Surface Water Quality: Have the Laws Been Successful? - RUTH PATRICK, Faith Douglass, Drew M. Palavage, and Paul M. Stewart (Princeton University Press, 2014)
In recent years the public has become increasingly concerned about the quality and quantity of surface waters. This book was written to examine the uses of surface waters by society and the effects of the resulting perturbations. Future policy options are discussed. The pollution of surface waters has steadily increased. This is because the direct domestic use by the rapid, increasing population and the products required for their lifestyle require more water. The consumptive use of water has also greatly increased, because of the greater demand for irrigation and cooling. The water uses of the increasing population have continually changed over time and have produced perturbations that were often not anticipated and have sometimes proved very difficult to measure. The populations have shifted and the waste products of the service industries and agriculture that serve them have changed continually. Great expansion in the use of boats for recreation has caused a severe pollution problem in many of our lakes, streams, and estuaries. Transcontinental shipping, which brings food and other commodities from all over the world, enters our estuaries and often causes severe pollution of these waters. Whereas, we have made definite attempts to control point sources of pollution, nonpoint source pollution remains a severe problem and one that is very difficult to control. In many of our surface waters nonpoint pollution is now our greatest problem. In order to control water pollution, many laws, both Federal and State, have been passed. The enforcement of these laws through regulations has largely been in the hands of the states, the exception being interstate rivers, which the Federal government also has a part in controlling. Laws have been passed and regulations have been made to control pollution, but often they have not been effectively enforced for some period of time after these regulations were put on the statute books. Billions of dollars of private and public monies have been spent to control pollution. Many questions are now being asked. How effective have these laws and regulations been? Should we change our approach toward solving the problems of water pollution? Amendments in the Clean Water Act are now actively being considered by Congress — should definite changes be made in order to improve the control of pollution, or should the same pattern of previous laws be followed? In this book we hope to answer some of these questions.